Infrared Based Relative Navigation for Active Debris Removal (ADR) - Yilmaz, Ozgun (Cranfield University, 2018)
3MT presented at the 2017 Defence and Security Doctoral Symposium.The risk of orbital collisions for operational satellites have been increasing overtime due to the uncontrolled space debris environment over years. The studies show that sustainable space environment can only be achieved by performing remediation actions such as ADR where a chaser spacecraft collects large space debris and perform necessary orbital disposal procedures. Even though overall mission has significant similarities with already demonstrated space Rendezvous and Docking (RvD) missions, they have more challenges due to uncertainties link to the target which is uncooperative. In this context, there are few technologies that need to be specifically developed and robust relative navigation is one of them. In current RvD missions, the relative navigation with cooperative targets are aided with RADAR, LIDAR which are not attractive due to limitations in spacecraft power budget and visual camera which suffers in certain illumination conditions. In this context, we propose infrared technologies as an alternative robust solution which have inherent advantage of illumination invariance as well as being resistant to damages caused by sun in the field of view. We have first proved that space debris is observable under space thermal environment. We have also demonstrated that there are trackable features and can be used for navigation purposes. From these findings, we have developed a robust infrared based relative navigation algorithm that can operate in ADR like applications.
Keywords: 'Space debris'; 'Relative navigation'; 'Infrared'; 'DSDS17 3MT'; 'DSDS17'; 'Space Science'; 'Astronomical and Space Sciences not elsewhere classified'